CULTURA PRIMÁRIA DE CÉLULAS DENTÁRIAS HUMANAS: COMPARAÇÃO DE MÉTODOS DE ISOLAMENTO DE LINHAGENS - Jantsch, Maiara Oliveira (2020)
Researches that seek new training to expand qualified as therapeutic therapies in the most varied areas become very relevant with regard to the development of less invasive and comparable techniques in relation to effectiveness. As a result, methodologies for culturing and obtaining cells are being widely studied and used in a variety of tissues, including dental. This work is arranged in a manuscript and aims to identify the main tissues and methods used to obtain primary cultures of human dental cells, comparing the establishment process and the morphological characteristics. The mentioned section presents a study that comprises the theoretical-practical scenario, in the context of complementarity, where an integrative review is carried out - with a search in the PubMed, Science Direct and LILACS databases, using the terms primary cell culture (primary cell culture) , teeth (teeth), stem cells (stem cells) and isolation (isolation), interspersed by the Boolean operator AND - and an experimental trial - which used voluntarily donated teeth. The literature survey resulted in 39 articles included, where the tissues most used were pulp of primary teeth and pulp of permanent teeth and the most applied technologies were Explant (EX) and Enzymatic Digestion (DE), with the use of Collagenase type I and Dispase . No practical segments were used, as well as in addition to the apical papilla, of patients ranging in age from 7 to 21 years, making a total of 49 aggregates, coming from 36 teeth, containing cells remained in culture between 8 to 10 weeks and were submitted to EX and DE (using only Type I Collagenase). The strains from the three tissues were created successfully and the only unsatisfactory result of this work was the EX method, when applied to pulp of primary teeth. The use of collagenase type I, without the association of Dispase, does not present any prejudice in the establishment of cell cultures, which implies a well-placed demonstration of the possibility of using the method in an optimized way. Based on the above, it is concluded that the study corroborates the prospects of searching and testing standardized and potentialized techniques regarding a possible clinical use, so that evidence of this fact was brought, associating the report and comparing three cell types in relation to two establishment methodologies. Thus, the data indicated reinforce the importance of continuing efforts in this direction, since research related to cell multipotency is extremely valid with regard to the development and improvement of tissue engineering, as well as in relation to biocompatibility tests, aiming at new therapeutic options.